Cytotoxic natural antibodies against human tumours: an option for anti-cancer immunotherapy? - Schwartz-Albiez, Reinhard; Laban, Simon Andreas; Eichmüller, Stefan B.; Kirschfink, Michael (Autoimmunity reviews, 2008)
Healthy individuals may contain in their peripheral blood antibodies which are able to destroy human tumour cells mediated either by complement-dependent cytotoxicity or by apoptosis. The largest proportion of these antibodies is of IgM isotype and directed against distinct tumour associated carbohydrate epitopes. Although the origin of these antibodies is not clear they seem to belong to the class of natural antibodies because they are not affinity matured and are encoded by distinct germ-line restricted gene families. It is most likely that this class of natural antibodies has in vivo an anti-tumour protective effect which may contribute to so-called tumour surveillance. On the other hand malignant tumour cells exert mechanisms to counteract such an antibody attack. These comprise soluble factors as well as cell surface expressed membrane complement regulatory proteins (mCRP). Further studies are needed to elucidate molecular mechanisms leading to either tumour destruction induced by natural antibodies or to overcome the protective strategies of the tumour against antibody attack.